Profits versus human rights : accountability for corporate complicity in human rights violations - Mathabathe, Rethabile (Department of Political Studies, 2015)
This thesis seeks to examine the interplay between business and human rights within the context of political transitions from authoritarian to democratic rule. In the wake of the globalisation process and the subsequent breakdown of the Westphalian state system, transnational corporations (TNCs) have acquired augmented powers at a global level where previously states had been the only players; and yet TNCs have none of the human rights obligations of states, particularly under international law. This dissertation aims to examine why this accountability lacuna exists in relation to corporations, specifically in relation to state-sponsored human rights violations in which TNCs are complicit.